1997
DOI: 10.1159/000268040
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Retinal Pigment Epithelium and Choriocapillaries after Laser Photocoagulation: Correlations between Scanning Electron, Transmission Electron and Light Microscopy

Abstract: Cell-to-cell interactions between retinal pigment epithelial (RPE) cells and vascular endothelium were examined by scanning electron microscopy, which demonstrates many facets of surface topography. The repair process after laser photocoagulation was characterized by a morphologically heterogeneous population of regenerated RPE cells, including normal-looking cells, macrophage-like cells and large elongated RPE cells. The macrophage-like and normal-looking RPE cells were predominantly seen adjacent to growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The RPE has a proliferative capacity, and it has been demonstrated that local proliferation occurs after injury. 32,33 However, until now, no in vivo study has shown that RPE cell proliferation is induced by Wnt/b-catenin signaling after laser photocoagulation. To measure RPE cell proliferation after laser photocoagulation, the number of EdUpositive cells in the laser-treated area was counted in whole mounts.…”
Section: Discussionmentioning
confidence: 99%
“…The RPE has a proliferative capacity, and it has been demonstrated that local proliferation occurs after injury. 32,33 However, until now, no in vivo study has shown that RPE cell proliferation is induced by Wnt/b-catenin signaling after laser photocoagulation. To measure RPE cell proliferation after laser photocoagulation, the number of EdUpositive cells in the laser-treated area was counted in whole mounts.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a wealth of evidence that thermal photocoagulation of RPE cells stimulates the biosynthesis of various pro-and antiangiogenic mediators [26][27][28] . Yoshimura et al [29] demonstrated that photocoagulation of cultured human RPE cells results in the production of TGF-␤ 2 , a potent inhibitor of vascular endothelial cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Permeability of radiolabelled macromolecular tracers across the EC barrier was determined as follows. Within one hour of laser treatment, a mixture of radiolabelled tracers-[methoxy- 3 (Operation Manual, Packard Instrument Co) was used to calculate radioactivity of the individual radionuclides. A ratio of the radioactivity from each of the lower wells to the total count was determined for each timepoint and expressed as the percentage equilibration.…”
Section: Permeability Studiesmentioning
confidence: 99%
“…Changes in retinal morphology after laser have been well described in rats, 3 rabbits, 4 monkeys, 5 and humans. 6 7 Although some laser energy may directly affect the retinal vessels, it is generally accepted that the major site of absorption is the RPE and choroid.…”
mentioning
confidence: 99%